(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Nowadays, Bestlink College of the Philippines encountered significant problems as we have students, faculty members, disabled persons, and senior citizens who suffered in stairs. The researchers conducted an escalator in MV. This study was conducted in the Novaliches, Quezon City campus. The researchers constructed an escalator by using several materials and equipment that are needed. The researchers cannot sustain the materials and equipment that were used. This study provides knowledge and learnings to the readers and future researchers about the importance of an escalator. This study utilizedgroup of re quantitative research methods. The researchers used purposive sampling in this study to select five mechanical engineers and five electrical engineers as respondents to answer the questionnaires. After the product was done, the researchers conducted a survey questionnaire and surveyed the two groups of respondents. The collected data will be processed using statistical tools and used to answer the statement of the problem. Through the gathered data, the researchers found out the following results. The two groups of respondents assessed the level of acceptability by using the Likert scale and obtained the weighted means of 3.32 for electrical engineers and 3.43 for mechanical engineers in terms of concept, design feasibility, mechanism, and presentation are; both results were interpreted as acceptable. The results stated that using PVC board as the main material for constructing the miniature achieved the researchers’ expectations. The results of the study showed that correct materials can achieve the expectations such as the toughness and quality of the project. The results of the study also showed that the proper handling of funds, correct methods, and a correct floor plan will lead to the success of the project.